A Grounded Theory of Music-Video Use in an Exercise Facility. Issue 3 (2nd July 2020) - Bird, Jonathan M.; Karageorghis, Costas I.
ABSTRACT: Purpose : Despite considerable interest in the effects of music in an exercise context, there is a dearth of research examining the use of music-videos. This is surprising given the ubiquity of this medium in exercise facilities. The present study sought to examine the impact of a music-video channel on the social process of exercising in a public exercise facility. Method : A grounded theory approach underpinned by pragmatism and symbolic interactionism was employed. Thirteen exercisers completed reflective diaries following each attendance at the facility over a 4-week period. Subsequently, 11 exercisers were interviewed regarding the impact of the music-video channel on the social process of exercising at the facility. Staff members' perspectives were deemed important throughout the iterative process of data collection and analysis. Accordingly, four staff members were interviewed with reference to the social process of managing an exercise facility that featured a music-video channel. Data were analyzed using open, axial, and selective coding. Results : The results provide support for a three-stage substantive theory that commences with the content of the music-video channel. The second stage depicts a series of moderators (e.g., exercise factors, temporal factors) that revolve around the core category, appraisal of the appropriateness of channel content. Lastly, a range of effects pertaining to exercisers and facility staff are predicted, and relevant social processes are expounded. Conclusion : Given the prevalence of music-video channels in contemporary exercise and health facilities, the substantive theory bears relevance to exercisers, health/performance practitioners, and researchers.